2010
DOI: 10.1159/000284351
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Diabetic Retinopathy: A Comparative Trial of Photography and Scanning Laser Ophthalmoscopy

Abstract: Aims: To evaluate the sensitivity and specificity of wide-field scanning laser ophthalmoscopy (WSLO) in the detection of referable diabetic eye disease, and to compare its performance with digital retinal photography. Methods: Patients enrolled into the study underwent non-mydriatic WSLO imaging, then single- and dual-field mydriatic digital retinal photography, and examination with slit lamp biomicroscopy, the reference standard. Grading of retinopathy was performed in a masked fashion. Results: A total of 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 34 publications
0
33
0
1
Order By: Relevance
“…39 Laser-based imaging techniques (such as scanning laser ophthalmoscopy or optical coherence tomography) may be promising as these methods are able to scan through smaller pupils and ocular media abnormalities. 39,40 Our study has several limitations. Because diabetic retinopathy requires life-long surveillance, long-term follow-up is critical to evaluating the effectiveness and sustainability of telemedicine.…”
Section: Discussionmentioning
confidence: 94%
“…39 Laser-based imaging techniques (such as scanning laser ophthalmoscopy or optical coherence tomography) may be promising as these methods are able to scan through smaller pupils and ocular media abnormalities. 39,40 Our study has several limitations. Because diabetic retinopathy requires life-long surveillance, long-term follow-up is critical to evaluating the effectiveness and sustainability of telemedicine.…”
Section: Discussionmentioning
confidence: 94%
“…In the landmark CRYO ROP study, the initial diagnosis of threshold disease in 12% of eyes was overruled on subsequent examination within three days by another examiner [24]. Inter-observer variation could be minimized if experts opined on an image rather than on a live patient [25]. Furthermore, with ROP training not being mandatory in medical college curricula in India and only few postgraduate courses in ophthalmology imparting indirect ophthalmoscopy training to residents and fellows, the so-called "gold standard" for ROP screening appears to be an inadequate tool in tackling the current burden, even as its relevance is being questioned the world over [26].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to slit lamp biomicroscopy as the reference standard, UWF images achieved a sensitivity of 83.6% compared to 82.9% for digital photography in the ability to identify referable disease. 26 One study reported at the 2011 Association for Research in Vision and Ophthalmology meeting has compared nonmydriatic UWF retinal imaging with the Optos P200MA to clinical trial gold standard mydriatic ETDRS-protocol 7 standard field stereoscopic photographs. 27 The sensitivity of nonmydriatic UWF images for detecting any DR and proliferative diabetic retinopathy (PDR) diagnosed on ETDRS photos were 99% and 73%, respectively, with a specificity of 100% and 99%, respectively.…”
Section: Uwf Retinal Imaging For Detection and Classification Of Drmentioning
confidence: 99%